La calidad: una lección aprendida de experiencia japonesa, para emular en las Mipymes (2014)
The article shows the identification implemented by Japanese industry strategies with which they could resurface, after being impacted its economy and infrastructure after the Second World War, despite its limited natural resources and being only a third of the Colombian extension, has managed and maintained as a world-class exporter. It reflects on current concept of quality in a globalized world with communication facilities in the commercial relations between producers and consumers. Implemented strategies were based on principles recommended and taught by Edwards Deming, Joseph Juran and Armand Feigenbaum quality; principles and strategies implemented Colombian SMEs, is expected to achieve competitiveness, reliability, loyalty and trust companies and their products.